Iridium(triNHC)-Catalyzed Transfer Hydrogenation of Glycerol Carbonate without Exogenous Reductants - Cheong, Yeon Joo; Lee, Mi Hyun; Byeon, Heemin; Park, Jiyong; Yu, Sungju; Jang, Hye Young (Catalysts, 2022)
The iridium(Ir) (triNHC = tri-N-heterocyclic carbene)-catalyzed transfer hydrogenation of glycerol carbonate (GC) is described in the absence of additional hydride sources. The described reduction provides a sustainable route to produce industrially-valuable formate and lactate with high turnover numbers (TONs). The bimetallic Ir(I) involving triNHC carbene ligands exhibits high TONs, and the reaction mechanism, including the bimetallic Ir(triNHC) catalyst, is proposed based on mechanistic studies.
Keywords: CO2; formate; glycerol carbonate; Ir(triNHC); transfer hydrogenation